Pendampingan Branding Wisata Dengan Pemanfaatan Sosial Media Sebagai Sarana Promosi Wisata Desa Penanggal Kabupaten Lumajang - Aurel salsabillah; Kalvin Edo Wahyudi; Ninik Dwi Marwanti; Nabilla Aziza Fajar Alfiyanto (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
At this time, the tourism sector in Indonesia began to develop, making most regions in Indonesia competing to increase the number of tourism enthusiasts in each region. Lumajang has great natural potential in the utilization and development of tourist villages. One of them is Penanggal Village, which is a tourist village in Candipuro District, Lumajang Regency, East Java. Penanggal Village consists of seven hamlets, namely Krajan Hamlet, Wonosari, Watukandang, Kemamang, Sumbersari, Gunung Gending and East Rekesan. Where in each hamlet there is a prominent tourism potential and human resources. By utilizing the beauty of nature and existing human resources. Tirtosari View is a natural bathing tour originating from the original springs of Mount Semeru located in Sumbersari Hamlet, Penanggal Village, this tour is a nature tour that has the only freshwater underwater in East Java and photo spot facilities in it. By presenting the view of Mount Semeru which is very enchanting, and its nature is still beautiful. make this tourist spot very natural. Therefore, a mentoring program is needed in terms of proper branding planning aimed at attracting many local and non-local tourists by introducing the tourism potential of Lumajang Regency.